2020
DOI: 10.3390/app10082895
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the OncomineTM Lung cfDNA Assay for Liquid Biopsy by NGS of NSCLC Patients in Routine Laboratory Practice

Abstract: Targeted next-generation sequencing (NGS) based on molecular tagging technology allowed considerable improvement in the approaches of cell-free DNA (cfDNA) analysis. Previously, we demonstrated the feasibility of the OncomineTM Lung cell-free DNA Assay (OLcfA) NGS panel when applied on plasma samples of post-tyrosine kinase inhibitors (TKIs) non-small cell lung cancer (NSCLC) patients. Here, we explored in detail the coverage metrics and variant calling of the assay and highlighted strengths and challenges by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…Thus, reporting from various studies by independent groups may help to determine the performance of the assay. The previous study using the Oncomine Lung Cell-Free DNA Assay, the same platform with the different assay, demonstrated a sensitivity of 81% with <20 ng of cfDNA at a VAF of 0.1%, whereas our data showed a sensitivity of 50% under the same condition [21]. In the report by the manufacturer, the same assay in the present study showed a sensitivity of 80% at a VAF of 0.1% for SNV [22].…”
Section: Discussionsupporting
confidence: 49%
“…Thus, reporting from various studies by independent groups may help to determine the performance of the assay. The previous study using the Oncomine Lung Cell-Free DNA Assay, the same platform with the different assay, demonstrated a sensitivity of 81% with <20 ng of cfDNA at a VAF of 0.1%, whereas our data showed a sensitivity of 50% under the same condition [21]. In the report by the manufacturer, the same assay in the present study showed a sensitivity of 80% at a VAF of 0.1% for SNV [22].…”
Section: Discussionsupporting
confidence: 49%
“…These include the droplet digital PCR (ddPCR) method with an estimated LOD of 0.05% for the exon 19 deletion and L858R mutations and 0.1% for T790M mutations 24 and the OncoBEAM (beads, emulsion, amplification and magnetics) approach with a LOD of nearly 0.02% for T790M mutation 25 . The conventional NGS-based approaches are considered less sensitive, however the implementation of a molecular tagging strategies in NGS technology in the last years allows to significantly reduce the sequencing artifacts and reach sensitivities similar to those observed with the other approaches (up to 0.1%) 26 , 27 .…”
Section: Discussionmentioning
confidence: 94%
“…Firefly assay demonstrated superior sensitivity and specificity with a 98.89% detection rate at an allele frequency of 0.2% [ 30 ]. Oncomine ™ Lung cell-free DNA Assay (OLcfA) NGS panel has been shown to be effective in detecting mutations in NSCLC patients with a detection limit of 0.1% [ 31 ]. In this proof-of-concept pilot study, we aim to develop and validate a custom 15-gene ctDNA NGS panel for detecting single nucleotide variants and small indels in lung cancer, with primary focus on EGFR mutation analysis in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our custom NGS panel showed comparable performance to the real time PCR based assays (Cobas and Therascreen) and achieved 100% analytical sensitivity and specificity for detecting EGFR mutations with at least 1% allelic frequencies. However, the assay is suboptimal when compared to droplet digital PCR or NGS-based assays which can achieve detection limits of below 1% [ 18 , 31 , 41 ].…”
Section: Discussionmentioning
confidence: 99%